Pengaruh Penerapan Project Based Learning (PJBL) dan Motivasi Belajar Terhadap Kemampuan Bernalar Kritis Siswa di SD Muhammadiyah Terpadu Ponorogo - Nuryanto, Edi; Prastiti, Tri Dyah; Wiryanto, Wiryanto (LP. Ma'arif Janggan Magetan, 2024)
This research aims to determine whether Project Based Learning (PjBL) and learning motivation on students' critical reasoning abilities in the Science Material of Forms of Substances and Their Changes at SD Muhammadiyah Terpadu Ponorogo partially or simultaneously. The population in this study were all fourth grade students at the Ponorogo Integrated Muhammadiyah Elementary School which consisted of 5 groups with a total of 130 students, while the sample was taken from 2 groups using random sampling to obtain a sample of 52 students. This research instrument uses a questionnaire for the variable implementation of Project Based Learning (PjBL) and student learning motivation, and uses a test for the variable students' critical reasoning abilities. Data analysis uses partial and simultaneous correlational analysis. For statistical testing, the SPSS version 25.0 program was used. The results of the research concluded that the application of Project Based Learning (PjBL) and student learning motivation had a very strong influence, both partially and simultaneously, on students' critical reasoning abilities in the Science Material of Forms of Substances and Their Changes at the Ponorogo Integrated Muhammadiyah Elementary School.